Using the effective belt and nearest neighbor equation to analyze the distribution of educational services in the new Halabja city - Majid, Mohammed Nooruddin Abdul Majid Abdul; Mohammed, Asst.Prof.Dr.Shad Hamid Mohammed (Sulaimani Journal for Humanities, 2025)
Educational services are among the most important urban services and a major need for residents of cities and surrounding areas. They have a significant impact on community life and are an effective tool for social, economic, cultural, and civilizational development. The study aims to find a balance in the distribution of educational services in the study area, To achieve this goal, we used the descriptive and analytical approach through several statistical and scientific tools within the Geographic Information System (GIS), such as (the nearest neighbor equation, the effect zone), In a way after applying the nearest neighbor equation, we found that the services were distributed randomly, and through the effect zone of the service, Through the scope of the service's impact, we also learned that there is a significant difference in the distribution of the different stages of the service, which are distributed unevenly, At the end of the study, we recommended building educational institutions for neighborhoods deprived of service, taking into account planning and population growth standards when building educational services using new technologies
Keywords: Educational Services; Distribution; Nearest neighbor equation; Effect zone